STUDI SEMIOTIKA: ANALISIS "GOLDEN SPOON" PADA DRAMA KOREA GHOST DOCTOR - Amarilia Shinta; K. Y. S Putri (SOURCE : Jurnal Ilmu Komunikasi, 2023)
Korean drama, which is one form of the Korean wave, is a favorite show in modern society today. One of the reasons why Indonesia can easily receive Korean Drama shows is that Asian culture is still close and common, such as stories that talk about love and self-sacrifice. Not only Indonesia, but South Korean drama fans are also from various countries. Seeing this, OTT (over the top) service providers flocked to buy broadcast rights from South Korean television broadcasters and from production houses. For example, a Korean drama entitled Ghost Doctor airs on the OTT Iqiyi and Viu platforms. The drama, which adopts the medical fantasy and comedy genre, tells of a resident doctor named Ko Seung Tak who is doing an internship at his family's hospital, Ko Seung Tak who also has a "golden spoon" economic status has a personality that is inversely proportional to Cha Young Min (Professor Cha). Professor Cha is described as a thoracic surgeon who is genius and arrogant, one day he has an accident so that the spirit of Professor Cha is able to enter Ko Seung Tak's body. Professor Cha uses Ko Seung Tak's body to save the patient. The purpose of this study is to examine the golden spoon in the drama Ghost Doctor through Charles Sanders Pierce's semiotic analysis consisting of sign, object, and interpretant. The results obtained are that there are five scenes of a golden spoon in Ghost Doctor Korean drama.